2019
DOI: 10.1088/1755-1315/387/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Hematological profile of sumba ongole cattle extensively reared in semiarid land, Sumba, NTT based on age and sex

Abstract: Hematological parameters have provided useful information about the animal health status. The main objective of the study was to measure the hematological profile of Sumba Ongole (SO) cattle extensively reared in semi-arid land in Sumba, NTT. Blood samples from seventy-five animals were examined to measure its hematological parameters based on age and sex. Animal were grouped based on sex into male and female in the age groups 1.5 to 3 years (n=42), 3.5 to 4 years (n=23) and ≥ 5 years (n=10). Mean standard err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The studies on rusa deer, sika deer (Cervus nippon yesoensis) and grey-brocket deer (Mazama gouazoubira) found low MCV values in males as well, but there were no significant differences between the males and the females [30][31][32]. Besides cervid, other animals like cattle was found low MCV values in males [33]. However, in rusa deer, HO et al (2018) found the MCV values for the females was significantly higher than the males [15].…”
Section: Discussionmentioning
confidence: 97%
“…The studies on rusa deer, sika deer (Cervus nippon yesoensis) and grey-brocket deer (Mazama gouazoubira) found low MCV values in males as well, but there were no significant differences between the males and the females [30][31][32]. Besides cervid, other animals like cattle was found low MCV values in males [33]. However, in rusa deer, HO et al (2018) found the MCV values for the females was significantly higher than the males [15].…”
Section: Discussionmentioning
confidence: 97%
“…The trait can be found in Australian beef cattle [ 30 ] and in some breeds of Indonesian beef cattle, such as the Peranakan Ongole (PO), the Belgian Blue × PO hybrid, and the PO × Pegolo Bali cattle [ 31 , 32 ]. However, the result might probably be different from other Ongole beef cattle extensively grazed under a harsh environment in a tropical semi-arid region, such as Sumba Island [ 33 ]. The PO breed of cattle is a crossbreed of the Java and Sumba Ongole (SO) breeds [ 32 ], while the SO cattle are one of Indonesia’s native beef cattle breeds, brought originally from India by the Indonesian Government in the earliest of 18th century.…”
Section: Introductionmentioning
confidence: 92%
“…The SO cattle have been extensively grazed on Sumba Island for genetic development [ 34 ]. Because of its benefits as a source of protein and its strong adaptability to harsh environmental conditions, this breed has been designated a nationally protected genetic resource [ 33 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…PO cattle are crossbreds of Java cattle and Sumba Ongole (SO) cattle, with SO cattle being one of Indonesia's native beef cows, introduced straight from India by the Indonesian government and extensively grazed on Sumba Island for genetic development (Gaina et al, 2020). They are well-known for their protein content and for being very adaptable to severe conditions, as seen on Sumba Island (Gaina et al, 2019;Sutarno and Setyawan, 2015). While we know that variations in a number of genes might affect reproductive ability, the role of the BMP 15 gene and its precise biological function in SO cattle has not been investigated.…”
Section: Introductionmentioning
confidence: 99%